Vestibular disease in dogs under UK primary veterinary care: Epidemiology and clinical management. (10th August 2020) - Radulescu, Sinziana Maria; Humm, Karen; Eramanis, Louis Mark; Volk, Holger A.; Church, David B.; Brodbelt, David; O'Neill, Dan Gerard
Abstract: Background: Vestibular disease (VD), central or peripheral, can be a dramatic primary‐care presentation. Current literature describes mostly dogs examined in referral centers. Hypothesis/Objectives: Describe the prevalence, presentation, clinical management, and outcomes of VD in dogs under primary veterinary care at UK practices participating in VetCompass. Animals: Seven hundred and fifty‐nine vestibular cases identified out of 905 544 study dogs. Methods: Retrospective cohort study. Potential VD cases clinically examined during 2016 were verified by reviewing clinical records for signalment, presenting clinical signs, treatments, and outcomes. Multivariable logistic regression was used to evaluate factors associated with VD. Results: The overall prevalence of VD was 8 per 10 000 dogs (95% CI = 7‐9). Median age at first diagnosis was 12.68 years (interquartile range [IQR], 11.28‐14.64). Compared with crossbreeds, breeds with the highest odds of VD diagnosis included French Bulldogs (odds ratio [OR] = 9.25, 95% CI = 4.81‐17.76, P < .001), Bulldogs (OR = 6.53, 95% CI = 2.66‐16.15, P < .001), King Charles Spaniels (OR = 4.96, 95% CI = 2.52‐9.78, P < .001), Cavalier King Charles Spaniels (OR = 3.56, 95% CI = 2.50‐5.06, P < .001), and Springer Spaniels (OR = 3.37, 95% CI = 2.52‐4.52, P < .001). The most common presenting signs were head tilt (69.8%), nystagmus (68.1%), and ataxia (64.5%). The most frequently used treatments were antiemetics (43.2%), systemic glucocorticoids (33.1%), antimicrobials (25%), and propentofylline (23.25%). There were 3.6% of cases referred. Improvement was recorded in 41.8% cases after a median of 4 days (IQR, 2‐10.25). Conclusions: Our study identifies strong breed predispositions for VD. The low referral rates suggest that primary‐care data sources offer more generalizable information for benchmarking to help clinicians review their own clinical activities.